Direct Effect of Problem-Solving Strategies, Communication, and Negotiation Styles towards Marital Satisfaction among Secondary School Teachers in Nigeria - Lukman, Fasasi; Khan, Aqeel; Abdu Bichi , Ado; Masud Ibrahim, Oniye (International Journal of Psychosocial Rehabilitation, 2020)
This study investigates the direct effect of problem-solving strategies, communication, and negotiation styles on marital satisfaction among secondary school teachers in Nigeria. To achieve the purpose, a cross-sectional survey design was adopted with a sample of 385 married couples in Kwara State, Nigeria. The instruments used are tagged ‘Problem-Solving Strategies, Communication, and Negotiation Styles towards Marital Satisfaction Scales’ and contained 80 items spread among the 16 sub-constructs; 4 Likert-type scales were adopted throughout the scale. The data collected were entered into Microsoft Excel 2016 and SPSS 20 for data cleaning and were filtered to SmartPLS 3. The data was checked for normality using two indicators of skewness and kurtosis. The data analysis was conducted using partial least squares structural equation modelling approaches with SmartPLS 3 software. The measurement models were evaluated by item loading, composite reliability (CR), and average variance extracted (AVE). The results revealed that the measurement model assessed in this study showed acceptability with validity and reliability test results presented in the preceding sections. The convergent validity is examined through the factor loadings, composite reliability (CR), and average variance extracted (AVE). Thus, with the effect of all the measurement requirements, it can be concluded that the direct effect of problem-solving strategies, communication, and negotiation styles on marital satisfaction scales validated in this study can be used to predict the direct effect of problem-solving strategies, communication, and negotiation styles on marital satisfaction among secondary school teachers in Nigeria.